[(5²-2.3²)² + (25/5)³ - (39/3)²]² ÷ (8²-7.3²)^5
Soluções para a tarefa
Respondido por
1
Olá.
![\dfrac{[(5^2-2\cdot3^2)^2+(25/5)^3 - (39/3)^2]^2}{(8^2-7\cdot3^2)^5}=\dfrac{[(25-2\cdot9)^2+(5)^3 - (13)^2]^2}{(64-7\cdot9)^5}=
\\\\\\\dfrac{[(25-18)^2+125 - 169]^2}{(64-63)^5}=\dfrac{[(7)^2-44]^2}{(1)^5}=
\dfrac{[49-44]^2}{1}=\dfrac{[5]^2}{1}=\\\\\\\dfrac{25}{1}=\boxed{\boxed{5}} \dfrac{[(5^2-2\cdot3^2)^2+(25/5)^3 - (39/3)^2]^2}{(8^2-7\cdot3^2)^5}=\dfrac{[(25-2\cdot9)^2+(5)^3 - (13)^2]^2}{(64-7\cdot9)^5}=
\\\\\\\dfrac{[(25-18)^2+125 - 169]^2}{(64-63)^5}=\dfrac{[(7)^2-44]^2}{(1)^5}=
\dfrac{[49-44]^2}{1}=\dfrac{[5]^2}{1}=\\\\\\\dfrac{25}{1}=\boxed{\boxed{5}}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5B%285%5E2-2%5Ccdot3%5E2%29%5E2%2B%2825%2F5%29%5E3+-+%2839%2F3%29%5E2%5D%5E2%7D%7B%288%5E2-7%5Ccdot3%5E2%29%5E5%7D%3D%5Cdfrac%7B%5B%2825-2%5Ccdot9%29%5E2%2B%285%29%5E3+-+%2813%29%5E2%5D%5E2%7D%7B%2864-7%5Ccdot9%29%5E5%7D%3D%0A%5C%5C%5C%5C%5C%5C%5Cdfrac%7B%5B%2825-18%29%5E2%2B125+-+169%5D%5E2%7D%7B%2864-63%29%5E5%7D%3D%5Cdfrac%7B%5B%287%29%5E2-44%5D%5E2%7D%7B%281%29%5E5%7D%3D%0A%5Cdfrac%7B%5B49-44%5D%5E2%7D%7B1%7D%3D%5Cdfrac%7B%5B5%5D%5E2%7D%7B1%7D%3D%5C%5C%5C%5C%5C%5C%5Cdfrac%7B25%7D%7B1%7D%3D%5Cboxed%7B%5Cboxed%7B5%7D%7D)
A imagem é pra caso o LaTex falhe.
Qualquer dúvida, deixe nos comentários.
Bons estudos.
A imagem é pra caso o LaTex falhe.
Qualquer dúvida, deixe nos comentários.
Bons estudos.
Anexos:
![](https://pt-static.z-dn.net/files/db9/c35b7fb43cfb39a597d5214601085feb.png)
Perguntas interessantes
Matemática,
11 meses atrás
Biologia,
11 meses atrás
Matemática,
11 meses atrás
Português,
1 ano atrás
Matemática,
1 ano atrás